EPIDERMOID CARCINOME ASSOCIATED TO CHRONIC INFESTATION BY HABRONEMA MUSCAE IN A HORSE PINTO RACE: REPORT OF A CASE IN VENEZUELA - Morales B, Abelardo (2008)
An 8 year old male Pinto horse (Equus caballus) had a history of chronic exudative nodular balanopostitis complicated by secondary bacterial infection dating back to 4 years. Severe chronic wasting, oliguria, stranguria, polydipsia and lymphoadenomegaly of bubos femurales and pre-scapular areas were noted. Euthanasia was performed. Later necropsy was performed systematically by the techniques described for horses. Tissue sections were taken for histopathological examination and were processed by conventional methods. Fecal samples were taken for parasitological studies. Gross examination revealed severe chronic wasting, and exudative balanoposthitis with severe chronic secondary bacterial infection. Evidenced hydroperitoneum lymphoadenomegaly of mesenteric nodes were also observed. Histological sections showed severe chronic balanoposthitis, with focal cell proliferation of squamous cell with abundant spin cells acanthosis, pleomorphism, nuclear hyperchromasia, anaplasia, typical mitotic figures, and atypical consistant presence of abundant pearls corneas. In some areas, granulomas were observed with parasite forms of the genus Habronema. Parasitological results were consistent with eggs of Habronema muscae. In conclusion, the clinical history, and macroscopic and histological findings demonstrate a syndrome of chronic balanopostitis and metastatic squamous cell carcinoma.